2007
DOI: 10.1182/blood-2006-06-029603
|View full text |Cite
|
Sign up to set email alerts
|

C-KIT, by interacting with the membrane-bound ligand, recruits endothelial progenitor cells to inflamed endothelium

Abstract: We investigated the role of c-Kit and the membrane-bound ligand (mbKitL) in endothelial progenitor cell (EPC) recruitment by microvascular endothelial cells (ECs). We demonstrated that inflammatory activation induced the expression of the mbKitL on ECs both in vitro and in vivo, and that recruitment of EPCs depended on c-Kit/mbKitL interaction. Depletion of endogenous c-Kit or inhibition of c-Kit enzymatic activity by imatinib mesylate prevented adhesion of EPCs to activated ECs both in vitro and in vivo, indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 31 publications
(44 reference statements)
1
72
0
1
Order By: Relevance
“…The results reported in Figure 4b demonstrated that both inflammatory cells and EPCs expressing c-Kit (Figure 4c) adhered to TECs and that adhesion was prevented ( Figure 4b) when TECs were silenced for IL-3 or for the mbKitL (Supplementary Figure S2B). Moreover, in line with the role of Akt in mediating cell adhesion (Dentelli et al, 2007), we found that Akt is also crucial for adhesion of EPCs and inflammatory cells to TECs (Figure 4b). To validate the contribution of the mbKitL in regulating EPC and inflammatory cell homing into active sites of angiogenesis, in vivo experiments were performed.…”
Section: Tec Characterization and Functional Behaviorsupporting
confidence: 81%
See 2 more Smart Citations
“…The results reported in Figure 4b demonstrated that both inflammatory cells and EPCs expressing c-Kit (Figure 4c) adhered to TECs and that adhesion was prevented ( Figure 4b) when TECs were silenced for IL-3 or for the mbKitL (Supplementary Figure S2B). Moreover, in line with the role of Akt in mediating cell adhesion (Dentelli et al, 2007), we found that Akt is also crucial for adhesion of EPCs and inflammatory cells to TECs (Figure 4b). To validate the contribution of the mbKitL in regulating EPC and inflammatory cell homing into active sites of angiogenesis, in vivo experiments were performed.…”
Section: Tec Characterization and Functional Behaviorsupporting
confidence: 81%
“…Moreover, the finding that a reduced expression of inter-cellular adhesion molecule-1, E-selectin and the mbKitL was detected after Akt blockade or depletion (Supplementary Figure S4C) confirms the crucial role of Akt in controlling IL-3-mediated biological events. As in the bone marrow niches (Flanagan et al, 1991), the mbKitL on proliferating endothelial cells acts as an adhesion molecule for EPCs in sites of neovascularization (Dentelli et al, 2007). To assess whether the constitutive expression of the mbKitL by TECs might also regulate inflammatory cell and EPC trafficking into angiogenic sites, an adhesion assay was performed in different experimental conditions.…”
Section: Tec Characterization and Functional Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…However, we were unable to detect EPCs incorporated into tumour newly formed vessels in both experimental conditions (mice injected with EPCs 2 or 3 weeks after tumour cell injection) (data not shown). Eventually, endothelial cells recovered from primary human tumours (TECs) (Bussolati et al, 2003), known to form tumour-derived neovasculature (Bussolati et al, 2003;Dentelli et al, 2007), were injected s.c. into SCID mice in the presence of IL-3, soluble Fc1.3, Fc1.4, Fc4 or the Fc fragments and used as an indirect tumoral angiogenic model. After 5 days, labelled EPCs were injected in the tail vein of these mice, and 2 days later, Matrigel plugs were recovered for immunostaining.…”
Section: Soluble Fc14 and Fc4 Fusion Proteins Impair H-end Migrationmentioning
confidence: 99%
“…In vivo EPC contribution to tumour neovasculature EPC contribution to tumour vascular growth was evaluated in DBA/2 mice (four mice for each experimental group) injected with H-END cells or in SCID mice injected s.c. with growth factor-reduced Matrigel containing endothelial cells derived from primary human tumours (TECs) (Bussolati et al, 2003;Dentelli et al, 2007), as described in detail in the online Supplementary data. The fraction of EPCs incorporated into tumoral vessels was calculated as a percentage of number of Fluorescein/Oregon Green-(Molecular Probes, Invitrogen) positive cells (antibody against CSFE marker) to the total number of CD31-positive stained vascular cells around microvessels (data not shown), counted in 10 randomly selected fields in six different samples.…”
Section: Isolation Of Epcs From Peripheral Blood Mononuclear Cellsmentioning
confidence: 99%